A Dél–Dunántúl gazdasági egységei – ahogy önmagukat látják - Gőbl, Edina (Tér és Társadalom, 1996)
The study attemp to sketch a picture of Southern-Transdanubia region, to show the point of view of the micro-sphere. This study based on a questionnaire what asked almost 300 enterprises, and firms, to collect their opinions about the regional development strategy. If the actors of the regional development wants to enforce and transmit the spatial, regional interests more efficient towards the economic sphere - which is less sensitive in this context - they have to know how they think about it, what are they opinions. When we analysed the primer information coming from the experts of the firms and enterprises, we have to recognise that fact, that the region placing in a transitional situation, as we think earlier. This situation determines the market-orientation, the self-picture of the economic actors. If we want a real development in the whole region, we have to transmit and built the new priorities into the bead of the economic actors, to influence they ideas, they behaviour.